DEVIATION FROM PUBLIC SERVICE ETHICS AND WAYS TO COMBAT IT -A COMPARATIVE STUDY (American Journal of Research in Humanities and Social Sciences, 2024)
The subject of public office ethics is considered one of the most important topics that are these bisect of our study at the present time, because these ethics represented the most important components of the job, which must be adhered to in order to audience the public job in public administration. The reality we live various public administration shows us manifestations of breaches of ethics public function of various types, the resulting damages, whether to the relationship between the administration and its employees or to the citizen or facility, were the result of subjective causes and factors liked to the person of the public employee, objective reason related to the administration itself and the functional environment, therefore, we had to put in place mechanisms to combat these violation issued by the administration employee and rationalization and rationalizing the ethics of the public job from any administrative violation and in order create and ensure the best administrative work activities administrative for any public administration, because the success of the lather in performing its tails achieving its goals, and achieving the result entrusted to it is an important matter and does not need confirmation because modern administration have become trait there and its sign, its a distinctive sign of modernity and development , and its his responsibility to provide public services to the citizen with a great lewd of quality mastery and with an integrity and transparency in order to reduce all manifestations of administrative forms and corruption.